IMPACT OF CEO CHARISMA ON FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIAN FIRMS - Anindya Apta Apsari; Dony Abdul Chalid (Berkala Akuntansi dan Keuangan Indonesia, 2023)
Charisma is a personal characteristic of a person that makes others view them as a leader. Some prior studies on CEO charisma and financial performance found a positive relationship between CEO charisma and their firm’s performance, especially during conditions of uncertainty. This study seeks to find the impact of CEO’s charisma on Indonesian firms’ financial performance, using firm risk as the uncertainty condition. This study picked some firms from IDX80 because the firms in that index are believed to have a higher market capitalization and more known by the public, thus giving the possibility of more news coverage. CEO’s charisma is calculated by doing text analysis on articles discussing these CEOs. Firm performance measures used were ROA and Tobin’ s Q. This study used firm risk measured from beta and epsilon of CAPM as a moderating variable to find whether firm risk act as a moderator to increase the effect of CEO’s charisma on firm performance. Panel data regression was used to determine relationship between the variables. This study found a positive and significant relationship between charisma and firm performance when Tobin’s Q was used as a dependent variable and firm-specific risk was included in the regression. However this study found no significant moderating variable by firm risk on the relationship between CEO charisma and firm performance.